Curve and double-layer economic dispatching considering reasonable wind abandonment under different time granularities - Gang, Zhang; Yue, Yang; Tuo, Xie; She, Zhang Kao; Xin, He (Frontiers in Energy Research, 2023)
In view of the large output of wind power during the load trough time, the peak regulation cost may increase sharply, and the traditional hourly dispatch may not be able to accurately track the load fluctuation due to the fluctuation of renewable energy. In this paper, based on different time granularity, an adaptive segmented double-layer economic scheduling model of net load curve considering reasonable wind abandonment is constructed. The model can better cope with net load changes while reducing the load peak-to-valley difference. Firstly, a reasonable wind abandonment model is established under different time granularity of 5 min, 15 min, 30 min and 1h;Then, based on the static thinking of the net load curve by time period, the load change in hourly scale is fully considered without changing the total number of dispatching periods, so that each dispatching period can adaptively select the duration according to the change of net load gradient, and a self-adaptive subsection model of net load curve is established to minimize the total running cost. Finally, taking IEEE-30 nodes as the example system, and NSGA-II algorithm and CPLEX solver are used to solve the model. The results verify the economy and feasibility of the proposed model.